A proposed information systems strategic plan of the University of the Philippines School of Library and Information Studies 2008-2013 - Simbol, Raffy, P. (School of Library and Information Studies, University of the Philippines Diliman, 2007)
The University of the Philippines School of Library and Information Studies is the premiere library school of the Philippines and Asia. It is the first library institution to capitalize on information technology embedding it to different Library and Information Science tracks. The school envisions to have high tech facilities to support the courses that it offers. To be able to obtain this vision, SLIS must have a plan on its acquisition, use and maintenance of its IT infrastructure.